A compact wide band textile MIMO antenna with very low mutual coupling for wearable applications. Issue 8 (1st April 2019) - Biswas, Ashim Kumar; Chakraborty, Ujjal
Abstract: This communication presents a compact wide band wearable MIMO antenna with very low mutual coupling (VLMC). The proposed antenna is composed of Jeans material. Two "I" shaped stubs are connected in series and are employed on the ground plane between the two patches separated by 0.048 λ to increase isolation characteristics of the antenna‐port. The antenna covers frequency spectrum from 1.83 GHz to 8 GHz (about 125.5%) where the minimum port isolation of about 22 dB at 2.4 GHz and maximum of about 53 dB at 5.92 GHz are obtained. The envelope correlation coefficient (ECC) of the MIMO antenna is obtained to be less than 0.01 with a higher diversity gain (DG > 9.6) throughout the whole operating band. The proposed MIMO antenna is cost effective and works over a wide frequency band of WLAN (2.4‐2.484 GHz/5.15‐5.35 GHz/5.72‐5.825 GHz), WiMAX (3.2‐3.85 GHz) and C‐band downlink‐uplink (3.7‐4.2 GHz/5.925‐6.425 GHz) applications. Simulation results are in well agreement with the measurement results.